Microwave‐Assisted Metal‐Free Decarboxylative Iodination/Bromination of Isoxazole‐4‐carboxylic Acids. Issue 11 (15th October 2019) - Barak, Dinesh S.; Dahatonde, Dipak J.; Batra, Sanjay
Abstract: A microwave‐assisted metal‐free route to substituted 4‐haloisoxazoles via decarboxylative halogenation of substituted isoxazole‐4‐carboxylic acids using N ‐iodosuccinimide (NIS) and N ‐bromosuccinimide (NBS) in the presence of K3 PO4 is described. It was discovered that the substitutions present at the 3‐position of differently 3, 5‐disubstituted isoxazoles influenced the outcome of the protocol. The methodology is compatible for performing decarboxylative halogenation followed by decarboxylative Suzuki‐Miyaura and Sonogashira couplings as one‐pot process. Abstract : Synthesis of 4‐haloisoxazoles from isoxazole‐4‐carboxylic acids via microwave‐assisted decarboxylative halogenation using NIS/ NBS is described.